Cadmium-Induced Cytotoxicity: Effects on Mitochondrial Electron Transport Chain - Branca, Jacopo Junio Valerio; Pacini, Alessandra; Gulisano, Massimo; Taddei, Niccolò; Fiorillo, Claudia; Becatti, Matteo (Frontiers in Cell and Developmental Biology, 2020)
Cadmium (Cd) is a well-known heavy metal, environmental toxicant and pollutant worldwide being largely present in every kind of item such as plastic (toys), battery, paints, ceramics, contaminated water, air, soil, food, fertilizers and cigarette smoke as well. Nowadays, it represents an important research area for the scientific community mainly for its effects on public health. Due to a half-life ranging between 15-30 years, Cd owns the ability to accumulate in organs and tissues exerting deleterious effects. Thus, even if at low doses, a Cd-prolonged exposure may cause a multi-organ toxicity. Mitochondria are key intracellular targets for Cd-induced cytotoxicity, but the underlying mechanisms are not fully elucidated. The present review is aimed to clarify the effects of Cd on mitochondria and, particularly, on mitochondrial electron transport chain (ETC).